Guillain–barre syndrome as a presenting feature of systemic lupus erythematosus in a child and it's complete resolution with rituximab treatment - Rahul Reddy; Anu Punnen; Annie Bella; Sathish Kumar (Indian Journal of Rheumatology)
Systemic lupus erythematosus (SLE) can present with varied neurological manifestations in children. Guillain–Barre syndrome (GBS) as a presenting feature of SLE is quite rare in children. We report a 9-year-old girl who presented with acute motor axonal polyradiculoneuropathy and noticed to have features of SLE. She was initially treated with intravenous immunoglobulins and corticosteroids with partial response. After starting rituximab, she showed dramatic recovery, proving the role of rituximab in GBS refractory to first-line medications in SLE. She remained in remission after 12 months of follow-up.